RUNWAY AND HIGHWAY GEOMETRIC DESIGN WITH CONSIDERATION OF HYDROPLANING RISK (Malaysian Journal of Civil Engineering, 2018)
Runway is multilane high speed corridor. Width of runway varies from 23 m to 60 m. An important aspect of runway and highway geometric design is ensuring prompt removal of water from the runway / highway to reduce skidding and hydroplaning risks of aircraft /highway traffic operating under wet-weather conditions. A methodology for runway and highway geometric design that incorporates hydroplaning consideration has been proposed to ensure safe operations. Cross-slope is the main geometric element affected by the hydroplaning consideration. This paper presents an independent simplified methodology for risk calculation against hydroplaning. This methodology determines whether a trial geometric design catering to the aircraft traffic and highway traffic meets the safety requirement against hydroplaning for the selected design rainfall. Critical texture depth has been found to be 0.5mm for airport pavement to avoid hydroplaning. Provision of side slope on one side is safer than that on both sides with regard to hydroplaning risk. Hydroplaning risk increases with increasing cross-slope of the runway for a known texture depth. Hydroplaning risk in highway is minimal and risk may be minimized by limiting vehicle speed to 40 kmph or lesser during raining